Coronavirus disease 2019 (COVID-19) incidence after exposures in shared patient rooms in a tertiary-care center in Iowa, July 2020–May 2021. (12th December 2022) - Trannel, Alexandra M.; Kobayashi, Takaaki; Dains, Angelique; Abosi, Oluchi J.; Jenn, Kyle E.; Meacham, Holly; Sheeler, Lorinda L.; Etienne, William; Kukla, Mary E.; Alsuhaibani, Mohammed; Holley, Stephanie; Strandberg, Kelsey; et al.
Abstract: The incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure in shared patient rooms was low at our institution: 1.8 per 1, 000 shared-room patient days. However, the secondary attack rate (21.6%) was comparable to that reported in household exposures. Lengthier exposures were associated with SARS-CoV-2 conversion. Hospitals should implement measures to decrease shared-room exposures.